Functional Modules of Minimal Cell Division for Synthetic Biology. Issue 6 (2nd April 2019) - Hürtgen, Daniel; Härtel, Tobias; Murray, Seán M.; Sourjik, Victor; Schwille, Petra
Abstract: Cellular reproduction is one of the fundamental hallmarks of life. Therefore, the development of a minimal division machinery capable of proper genome condensation and organization, mid‐cell positioning and segregation in space and time, and the final septation process constitute a fundamental challenge for synthetic biology. It is therefore important to be able to engineer such modules for the production of artificial minimal cells. A bottom‐up assembly of molecular machines from bulk biochemicals complemented by in vivo experiments as well as computational modelling helps to approach such key cellular processes. Here, minimal functional modules involved in genome segregation and the division machinery and their spatial organization and positioning are reviewed, setting into perspective the design of a minimal cell. Furthermore, the milestones of recent in vitro reconstitution experiments in the context of cell division are discussed and their role in shedding light on fundamental cellular mechanisms that constitute spatiotemporal order is described. Lastly, current challenges in the field of bottom‐up synthetic biology as well as possible future developments toward the development of minimal biomimetic systems are discussed. Abstract : Cellular reproduction is one of the fundamental hallmarks of life . Hence, the development of a minimal division machinery constitutes a fundamental challenge for bottom‐up synthetic biology. Here, minimal functional modules involved in genome segregation and the division machinery, and their spatial organization and positioning are reviewed, setting into perspective the design of a minimal cell.